Effective hydro-mechanical material properties and constitutive behaviors of meso-structured RVE of saturated granular media. (November 2020) - Li, Xikui; Zhang, Songge; Duan, Qinglin
Abstract: In the framework of the second-order concurrent computation homogenization method for saturated granular material, meso-structured RVE (Representative Volume Element) is modeled as a compact assembly of saturated discrete particles. The boundary conditions imposed on the RVE are comprised of the two parts: (1) the boundary displacements and pressures prescribed by downscaled macroscopic strain variables and pore pressure, and (2) constrained fine scale fluctuations of mesoscopic hydro-mechanical variables expressed in terms of periodic boundary conditions. The present paper focuses on the estimation of effective hydro-mechanical material properties and constitutive behaviors of meso-structured RVE of saturated discrete particle assembly via a proposed homogenization procedure. To achieve this target, a novel scheme for determining and imposing periodic boundary conditions on peripheral particles contacting with the RVE boundary of saturated discrete particle assembly is proposed. Numerical results demonstrate performances and capabilities of the proposed scheme in estimating effective hydro-mechanical non-linear material properties and predicting hydro-mechanical constitutive behaviors of saturated granular materials evolving with loading histories. They also demonstrate the significance and necessity of imposing periodic boundary conditions on the RVE in proper prediction of effective hydro-mechanical material properties and constitutive behaviors.